2010
DOI: 10.1097/prs.0b013e3181cb675f
|View full text |Cite
|
Sign up to set email alerts
|

Perfecting the Design of the Gluteus Maximus Perforator–Based Island Flap for Coverage of Buttock Defects

Abstract: The flap design for coverage of gluteal defects has a great impact on recurrence and complications. This design is novel and the flap is simple to elevate. This is an ideal flap in any high-risk patient in whom the risk of recurrence is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 9 publications
2
38
0
Order By: Relevance
“…Taylor and Palmer reported in an angiosome study that more than 300 perforators with a diameter larger than 0.5 mm supplying the skin territory exist and that several perforators are present at the parasacral, gluteal, posterior thigh, and back areas for flap selection [8,27]. Regarding source artery selection in our procedure, similar to that in studies by Higgins et al and Kim et al [28,29], we used the flaps supplied by superior gluteal artery perforators for most of the sacral pressure sore reconstruction. The ischial pressure sores were mainly reconstructed using the flaps supplied by inferior gluteal artery perforators.…”
Section: Discussionsupporting
confidence: 82%
“…Taylor and Palmer reported in an angiosome study that more than 300 perforators with a diameter larger than 0.5 mm supplying the skin territory exist and that several perforators are present at the parasacral, gluteal, posterior thigh, and back areas for flap selection [8,27]. Regarding source artery selection in our procedure, similar to that in studies by Higgins et al and Kim et al [28,29], we used the flaps supplied by superior gluteal artery perforators for most of the sacral pressure sore reconstruction. The ischial pressure sores were mainly reconstructed using the flaps supplied by inferior gluteal artery perforators.…”
Section: Discussionsupporting
confidence: 82%
“…Compared to gluteal flaps, TFL flaps have not been favored because of the short vascular pedicle and bulkiness of the flap. 22,23 However, some authors reported that TFL perforators are constant and reliable, and easily identified on the lateral aspect of the proximal thigh. 22Y24 This makes the application of perforator flaps to the trochanteric region feasible.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to reconstruction of a large sacral soft tissue defect, options for reconstruction of a large gluteal soft tissue defect have seldom been discussed in the literature. 11,12 In many of the sacral-area reconstruction cases, the patients are looking for improvement in quality of life, or simply a closed wound situation. However, the scenario we present is for esthetic reconstruction of the gluteal area in very young patients, who expect not only reconstruction, but a good esthetic outcome, in the face of a reconstruction that is sometimes a lot more challenging than what we routinely deal with in the pressure sore scenario.…”
Section: Discussionmentioning
confidence: 99%